Abundant soliton solutions in saturated ferromagnetic materials modeled via the fractional Kraenkel–Manna–Merle system - Loubna Ouahid; Maryam Alshahrani; A. Mohamed Abdel-Baset; M. A. Abdou; Ali Akgül; Murad Khan Hassani (Scientific Reports)
Abstract The Modified Generalized Riccati Equation Mapping Technique is employed to discover novel solutions for the Fractional Kraenkel–Manna–Merle system. In this system, a nonlinear of ultra_short wave pulse propagates across saturated ferromagnetic-materials by very low conductance. The beta-derivative is used to analyze the fractional performance of the proposed system. Combo-multi soliton shape, anti-bell-shaped solitons, kink bright-dark shape are the results of the applications. The results obtained are original and unfamiliar to the reader, as they had not been published previously. For a few chosen solutions, two dimensional, and three dimensional are shown to offer important insights into the behavior and properties of the solutions. These detailed exact solutions and wave phenomena contribute to a deeper understanding of this equation. This work opens up new possibilities for exploring wave phenomena in more complexly structured nonlinear.